2022
DOI: 10.5334/paah.188
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environment on Physical Activity Levels and Obesity among Saudi Arabia Youth: Comparison of Urban; Rural Farm and Rural Desert Geographical Locations

Abstract: Background:The inactive lifestyle is becoming prevalent in many developed and developing countries including Saudi Arabia. Thus, the aim of this study was to evaluate the impact of neighborhoods' characteristics on physical activity (PA) levels and body mass index (BMI) in Saudi adolescents. Methods:The anthropometric measurement of 380 secondary-school (boys = 199; girls = 181) from different geographical locations such as urban, rural farm and rural desert was taken using the Seca digital scales for weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…For instance, females were reported to be less active than males, and participants from rural desert locations were also reported to be less active compared to other geographical areas. The current findings align with previous studies of a similar nature [8,42,53]. Furthermore, results regarding social ecological determents to Al-Ahsa youth participating in PA were interesting.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, females were reported to be less active than males, and participants from rural desert locations were also reported to be less active compared to other geographical areas. The current findings align with previous studies of a similar nature [8,42,53]. Furthermore, results regarding social ecological determents to Al-Ahsa youth participating in PA were interesting.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in this study, the Arabic version of the IPAQ-E was used. For more information about the IPAQ-E version including translation process referred to [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, studies have focused on individual demographics and psychological correlates to promote PA and prevent obesity [ 21 , 22 , 23 ]. The influence of cultural and environmental characteristics are expected to have a long-term and significant impact on the population, which could lead to the short-term effects of individually targeted interventions [ 24 , 25 , 26 ]. For instance, individuals from countries where PA is regarded as important for health are more likely to perceive fewer barriers, and therefore, engage in more regular PA compared to countries where PA is not a social norm [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, women living in urban areas reported having higher mean values for waist and hip circumferences and skinfold thicknesses, as well as for lean body mass and total fat, compared to those living in the rural areas of Kaur and Talwar [ 4 , 20 , 21 ]. Comparative results show that people from rural areas were reported as engaging in larger amounts of PA compared to their counterparts living in urban areas [ 22 , 23 ]. Previous research reported that the availability and accessibility of facilities in close proximity, including parks, were linked to higher PA engagement, especially in girls, whereas close proximity to retail stores was associated with boys’ PA engagement [ 24 ].…”
Section: Introductionmentioning
confidence: 99%